2016
DOI: 10.1371/journal.pone.0169021
|View full text |Cite
|
Sign up to set email alerts
|

Two Genotypes of Coxsackievirus A2 Associated with Hand, Foot, and Mouth Disease Circulating in China since 2008

Abstract: Coxsackievirus A2 (CV-A2) has been frequently detected and commonly associated with hand, foot, and mouth disease (HFMD) in China since 2008. However, limited sequences of CV-A2 are currently available. As a result, we have been focusing on the genetic characteristics of CV-A2 in the mainland of China during 2008–2015 based on national HFMD surveillance. In this study, 20 CV-A2 strains were isolated and phylogenetic analyses of the VP1 sequences were performed. Full-length genome sequences of two representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Previous studies have classified CV-A2 into four genotypes, namely, genotypes A, B, C, and D, in which genotypes are distinguished based on least 15% divergence in the VP1 nucleotide sequence [ 12 ]. Genotype C can be further divided into the C1 to C3 sub-genotypes, which exhibit more than 8% divergence in the VP1 region [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have classified CV-A2 into four genotypes, namely, genotypes A, B, C, and D, in which genotypes are distinguished based on least 15% divergence in the VP1 nucleotide sequence [ 12 ]. Genotype C can be further divided into the C1 to C3 sub-genotypes, which exhibit more than 8% divergence in the VP1 region [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we expanded the surveillance scope in that collected 74 new strains which were not included in HFMD cases isolated in previous study [ 12 ], and accomplished a more comprehensive molecular epidemiological analysis of CV-A2 from all six regions in mainland of China, and analyzed based on a long time span of 2008–2017. Earlier studies have classified CV-A2 into four genotypes, genotypes A, B, C, and D. In this study, we further divided genotype C into the C1 to C3 sub-genotypes in order to better explain genotype C. According to the previous genotyping rules, all 74 strains isolated in the present study were grouped under genotype D. Interestingly, genotype D was only found in China since 2008, which need continuous surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For E6, CVA2, CVA13, E7, CVA2 and EV-A71 the sequences D'Amori (AY302558.1), Fleetwood (AY421760.1), Flores (AF499637.1), Wallace (AF465516.1), Faulkner (AF114383.1) and BrCr (U22511) were used as reference strains, respectively. Reference sequences for viral genogroups, genotypes and/or clusters were also included [17,[20][21][22]. VP1 sequences were edited using Bioedit (7.2.5.0)/SeqMan (7.0.0) programs and aligned by Muscle [23].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…2), and a study in China reported a similar situation. 7 In conclusion, we report a recombinant CVA2 isolated from children with AFP in Taiwan. Because the CVA2 has an outbreak potential, and this CVA2 strain has a high risk of unfavorable neurological outcomes, children with AFP should be examined for the presence of CVA2 and other pathogenic EVs.…”
Section: Resultsmentioning
confidence: 75%